Carpal Dimensions by Plain Wrist Radiography in Patients with Severe Carpal Tunnel Syndrome. (30th March 2022) - Saeed-Banadaky, Seyyed Houssein; Rahimian, Hossein; Sobhan, Mohammad Reza
Abstract : In this study, we evaluated the diagnostic value of carpal dimensions in wrist plain radiography for the screening of carpal tunnel syndrome (CTS). This is a case-control diagnostic probe in which patients with severe CTS documented by electrodiagnostic study and healthy subjects as controls were enrolled. In the posteroanterior view of the wrist plain radiography in both groups, we defined and measured the carpal ratio, and the results were analyzed deploying statistical software. In this study, 119 participants, including 50 patients and 69 healthy subjects, were recruited. According to the ROC chart, the cutoff points, positive and negative predictive values, and the diagnostic accuracy for the cutoff points were calculated.